Sintesa dan Karakterisasi Material Ceramic Metal Composite (Ti1-xMox)C-NiCr melalui Proses Pemaduan Mekanik dengan Variasi Komposisi Molibdenum - Ali Alhamidi; Suryana Suryana; Saddam Husein (Jurnal Teknika, 2015)
Powder mixtures of Ti, Ni, Cr and C with various composition of  Mo are processed by planetary ball mill for 10 h and subsequently, sintered at temperatur of  1100 C for 2 h have been investigated. The result shows that wettability of titanium carbides enhanced with the fraction of molybdenum. Furthermore, the XRD and SEM observation show that TiC grains are refined, indicating Mo is an affective grain growth inhibitor.